Pengaruh kompensasi dan self efficacy serta work life balance terhadap job satisfaction - Nisa, Erika Choirun; Agustin, Ni Ketut Yulia Agustin Ketut Yulia (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
Job satisfaction among employees is important because high job satisfaction will result in a positive attitude toward workers, which will have an impact on improving company performance. Job satisfaction is not an independent aspect; however, there are several factors that influence both the external aspect (in the form of compensation, the internal aspect in the form of self-efficacy, and the employee’s relationship with work in the form of work-life balance. This study aims to determine the effects of compensation, self-efficacy, and work-life balance on the job satisfaction of PT employees. Delami Brand Kharisma Busana in Surabaya. This research method uses a quantitative approach with a sample of all PT employees. Delami Brands Kharisma Busana in Surabaya collected primary data using a Likert scale questionnaire. The variables used were compensation (X1), self-efficacy (X2), work–life balance (X3), and job satisfaction (Y). The data analysis was performed using multiple linear regression with SPSS version 25 software. The results indicate that there is a positive and significant effect of the compensation variable (X1), self-efficacy (X2), and work-life balance (X3) on the job satisfaction of employees at PT. Delami Brands Kharisma Busana is from Surabaya; thus, the coefficient of determination obtained was 51.2% of the independent variables used in this study. Keywords: Compensation, self efficacy, work life balance, job satisfaction.